4. Conditions for Access of the Poor to Microfinance Services: the Views of the Rural Financial Institution Officers in Lombok, Indonesia - Ketut Budastra (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2007)
Abstract This paper discusses main issues useful for the provision of financial services to the poor. The discussion is based on the view of 23 officers of major Rural Financial Institutions (RFIs) in Lombok, Indonesia. Data collected through in-depth interviews using an open-ended questionnaire in 2007. It was found that providing rural-micro financial services can be financially feasible, cost-effective if three fundamental issues are dealt properly: These issues are: the poor had insufficient physical collateral; the poor had very limited knowledge and experience in banking; and the poor generally do not have permanent businesses. Suggested strategies are, as follows. Rural financial institutions (RFIs) should lend loans to those who have good characters and businesses; and implement adaptive and convenient service policy and mechanism. Contract enforcement is in=effective for group lending. Frequent visits, supervision and monitoring, good applicant screening and field officer incentives were among the instruments considered able to increase loan repayment of the poor. Fair regulatory and market environment is necessary for RFIs to sustain their services. Abstrak Paper ini mendiskusikan beberapa isu-isu penting untuk penyediaan jasa keuangan untuk si miskin secara berkelanjutan. Diskusi didasarkan pada pendapat 23 pengurus Lembaga Keuangan Pedesaan di Lombok, yang dikumpulkan dengan tehnik interview mendalam pada tahun 2007. Respondent dipilih berdasarkan kesediaan mereka untuk diwawancarai. Ditemukan bahwa penyediaan jasa keuangan mikro dapat secara financial layak dan menguntungkan jika tiga isu-isu dasar dapat disiasati dengan baik. Ketiga isu-isu dasar tersebut adalah: si misin tidak punya jaminan yang memadai; si miskin memiliki pengetahuan dan pengalaman urusan bank yang terbatas; dan kebanyakan si miskin tidak memiliki usaha yang permanen. Strategi penanganan isu-isu tersebut adalah sebagai berikut. Lembaga keuangan pedesaan hendaknya memberikan pinjaman pada yang memiliki karakter dan usaha yang layak. Lembaga keuangan pedesaan hendanya menerapkan kebijakan dan meanisme pelayanan yang sederhana, mudah dan sesuai dengan karakter si miskin. Pinjaman secara kelompok adalah tidak effektip dalam penegakan perjanjian kredit. Kunjungan sering, pengawasan dan monitoring, seleksi nasabah yang baik, dan insentip tenaga lapangan merupakan instrumen untuk meningkatkan pengembalian kredit. Regulasi and lingungan pasar yang adil diperlukan oleh lembaga keuangan pedesaan untuk dapat memberikan pelayanan secara berkelanjutan.